PENGEMBANGAN INTERACTIVE DIGITAL BOOK BERBASIS SELF REGULATED LEARNING TERINTEGRASI NILAI KARAKTER PADA MATA KULIAH MANAJEMEN PENDIDIKAN - Masri Peranginangin, Laurensia; Tamba, Robenhart; Halimatusakkdiah; Free Unita Manurung, Imelda; Abda’u Ansya, Yusron (Universitas Negeri Medan, 2025)
Abstract: Higher education has a significant responsibility in producing a superior generation that is not only academically intelligent but also has character. However, the dominance of conventional methods such as lectures and the limited availability of printed learning media are obstacles in encouraging student learning independence. This study aims to develop an interactive multimedia e-book based on Self-Regulated Learning (SRL) that integrates character values in the Educational Management course. The research method uses Research and Development (R&D) with the ADDIE model, which includes needs analysis, design, development, implementation, and evaluation. The research subjects were students taking the Educational Management course in the Elementary School Teacher Education Program, Medan State University, with data obtained through interviews, questionnaires, and observations to assess the effectiveness of the e-book on learning outcomes and character formation. The results show that the interactive e-book based on SRL is proven to be effective in improving student learning outcomes. The average pretest score of 70.39 increased to 90.27 in the posttest, with an increase of 19.88 points or 28.25%. The N-Gain value of 0.67 is in the medium-high category, indicating optimal improvement in abilities. Thus, SRL-based interactive e-books are worthy of being used as an innovative strategy to improve the quality of learning while simultaneously shaping the profile of superior prospective student teachers. Keyword: Interactive Digital Books, Self-Regulated Learning, Character Values, Educational Management Abstrak: Pendidikan tinggi memiliki tanggung jawab besar dalam mencetak generasi unggul yang tidak hanya cerdas secara akademik, tetapi juga berkarakter. Namun, dominasi metode konvensional seperti ceramah dan keterbatasan media pembelajaran cetak menjadi hambatan dalam mendorong kemandirian belajar mahasiswa. Penelitian ini bertujuan mengembangkan e-book multimedia interaktif berbasis Self-Regulated Learning (SRL) yang terintegrasi nilai karakter pada mata kuliah Manajemen Pendidikan. Metode penelitian menggunakan Research and Development (R&D) dengan model ADDIE yang meliputi analisis kebutuhan, perancangan, pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah mahasiswa yang mengambil mata kuliah Manajemen Pendidikan Program Studi PGSD, Universitas Negeri Medan, dengan data diperoleh melalui wawancara, angket, dan observasi untuk menilai efektivitas e-book terhadap hasil belajar dan pembentukan karakter. Hasil penelitian menunjukkan bahwa e-book interaktif berbasis SRL terbukti efektif meningkatkan hasil belajar mahasiswa. Rata-rata nilai pretest 70,39 meningkat menjadi 90,27 pada posttest, dengan kenaikan 19,88 poin atau 28,25%. Nilai N-Gain sebesar 0,67 berada pada kategori sedang–tinggi, menandakan peningkatan kemampuan yang optimal. Dengan demikian, e-book interaktif berbasis SRL layak digunakan sebagai strategi inovatif untuk meningkatkan kualitas pembelajaran sekaligus membentuk profil mahasiswa calon guru yang unggul. Kata Kunci: Interactive Digital Book, Self Regulated Learning, Nilai Karakter, Manajemen Pendidikan